Community-Based Decision Making and Priority Setting Using the R Software: The Community Priority Index. (26th February 2015) - Salihu, Hamisu M.; Salinas-Miranda, Abraham A.; Paothong, Arnut; Wang, Wei; King, Lindsey M.
Abstract : This paper outlines how to compute community priority indices in the context of multicriteria decision making in community settings. A simple R function was developed and validated with community needs assessment data. Particularly, the first part of this paper briefly overviews the existing methods for priority setting and reviews the utility of a multicriteria decision-making approach for community-based prioritization. The second part illustrates how community priority indices can be calculated using the freely available R program to handle community data by showing the computational and mathematical steps of CPI (Community Priority Index) with bootstrapped 95% confidence intervals.